Review of Big Data Science and its relation with Cloud Technology - Milan, R; Pandey, KK; Shukla, D (International Journal of Computer Sciences and Engineering, 2025)
Big data science is the new emerging term in the field of computer technology. During the emergence of computer science the database is used to store the data but with the emergence of social networking sites the data is generated exponentially that is not able to store in the conventional method of storage so the new technology is derived that is used to store data in cloud technology. Cloud technology is a technology that is used to store data in a safe and secure manner. And it also gives the opportunity to use the data when required. We can mine the data with data mining algorithm and take decisions on the basis of that data